Sistem Forum Atas Talian Pelajar UTHM, UTHM Student Online Forum System - Harith Iskandar Saiful Fahme; Selamat, Norhanim (Applied Information Technology And Computer Science, 2021)
UTHM Student Online Forum System is a system that uses web technology to solve the problem of accessibility of UTHM student information. In implementing projects involving software engineering, methodology selection is one of the important aspects that ensure smoothness and effectiveness in system construction. The methodology that will be used in developing the UTHM Student Online Forum System is a prototype model. This system is expected to provide a new method for students to communicate as a forum to solve problems and inquiries faced by students. " UTHM Student Online Forum System " can provide a new communication medium to the users involved. This system can make it easier for its users, namely UTHM citizens, to share information and information between them. This system can also help new students who lack contacts from UTHM residents to obtain important information. In addition, users will get many benefits with this system. The problem of accessibility of information among UTHM students can be solved with the existence of this system.